Local Coffee Product Development Strategy - Nazla kaylasalma; Virgo Simamora (Jurnal Indonesia Sosial Teknologi, 2024)
Kopi Kali Place is one of the popular coffee shops in the North Jakarta area that has been established since 2019. The purpose of this study is to determine the market penetration and development of local coffee products of Coffe shop Kopi Kali. This study uses a descriptive qualitative approach to understand the development of local coffee products in Kopi Kali Coffee shop. The research methods used include in-depth interviews, participatory observation, documentation, and data triangulation. The results of the research show that Kopi Kali Coffee shop, since its establishment in 2019 until 2024, has undergone an impressive evolution in facing challenges and changes in the coffee industry. With strong adaptability and a high commitment to innovation, Kopi Kali has successfully developed an effective market penetration strategy. The main focus on innovative product development such as the transformation of "Kopi Belies" into a non-alcoholic version and the introduction of a variety of excellent coffee menus demonstrates a dedication to maintaining quality and creating a variety of flavors that appeal to customers. Smart marketing strategies, including the use of social media and partnerships with influencers, have been successful in increasing brand awareness and reaching a wider market segment.